Pemanfaatan Media Sosial Facebook dan Instagram Sebagai Upaya UMKM Sumber Rejeki Dalam Mempertahankan Usahanya di Masa Pademi Covid-19 - Diana Permata Sari; Sri Hartini (Perkumpulan Kualitama Edukatika Indonesia, 2021)
Micro, Small and Medium Enterprises (MSME) are businesses capable of encouraging the Indonesian economy to become better and more advanced. One of the MSME that still survived during the covid-19 period is the Sumber Rejeki MSME by producing onion crackers in Papringan Village, Kaliwungu District, Semarang Regency. So far, the marketing carried out by Sumber Rejeki MSME is still conventional, so the sales are still very low. Therefore, a new strategy is needed to develop MSME by using promotion through social media, Facebook and Instagram. Through social media, Facebook and Instagram can help MSME to promote their products. The output of this Community Service Program (CSR) activity is that it can help MSME to expand market share and increase sales turnover at MSME even though they have not been seen significantly. The benefits obtained from this activity are MSME becoming aware of technological developments and MSME have the skills to promote their products through social media, Facebook and Instagram. In addition, this activity is more cost effective and time efficient because it is carried out online.